A profitability analysis of small-scale plants for biomethane injection into the gas grid. (20th May 2018) - Cucchiella, Federica; D'Adamo, Idiano; Gastaldi, Massimo; Miliacca, Michela
Abstract: Biomethane is a promising renewable energy carrier with the potential to diversify and decarbonise natural gas. It is produced from a range of waste sources and can be distributed into the natural gas grid or used as a vehicle fuel or converted into in cogeneration units. The economic evaluation of small plants for biomethane injection into the gas grid is not well defined in literature. This paper proposes a mathematical and economic model useful to evaluate the profitability of these plants in according to Discounted Cash Flow (DCF) method. The indicators used are Net Present Value (NPV), Discounted Payback Time (DPBT), Internal Rate of Return (IRR) and Profitability Index (PI). The baseline case studies analyse three different small-scale sizes (50 m 3 /h, 100 m 3 /h and 150 m 3 /h) concerning two typologies of substrates (organic fraction of municipal solid waste (ofmsw) and a mixture of maize and manure residues). Results define that the profitability is verified only for 150 m 3 /h ofmsw plant in baseline case study (NPV is 615, 694 €, DPBT is 3 y, IRR is 33% and PI is 0.18). Furthermore, alternative case studies are conducted on the main critical variables (subsidies, investment costs of biogas production, transport costs of substrates and percentage of maintenance and overhead costs in biogas production). The economic feasibility can be reached in the following case studies: 100 m 3 /h ofmsw plant in sensitivity analysis, 50 m 3 /h ofmsw plant in scenario analysis, 150 m 3 /h mixed plant in scenario analysis with a new incentive scheme and 100 m 3 /h manure residues plant in scenario analysis. The biomethane can contribute to develop the circular economy recovering a wide range of waste. Highlights: Biomethane obtained by organic fraction of municipal solid waste is profitable. Biomethane obtained by 70% manure residues and 30% energy crops is unprofitable. Biomethane obtained by manure residues is unprofitable. Plants' size influences significantly Net Present Value. Subsidies play a key-role in an economic evaluation.